2000
DOI: 10.1104/pp.124.3.959
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Expansion in Polarly Growing Root Hairs ofMedicago truncatula

Abstract: Fluorescent microspheres were used as material markers to investigate the relative rates of cell surface expansion at the growing tips of Medicago truncatula root hairs. From the analysis of tip shape and microsphere movements, we propose three characteristic zones of expansion in growing root hairs. The center of the apical dome is an area of 1-to 2-m diameter with relatively constant curvature and high growth rate. Distal to the apex is a more rapidly expanding region 1 to 2 m in width exhibiting constant su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 30 publications
5
65
0
1
Order By: Relevance
“…A targeted secretion could have the effect of locally weakening the cell wall and allowing turgor-driven cell expansion. In this regard it is pertinent that studies of root hairs, which like the pollen tubes grow by tip expansion, show that the region of maximal shape change at the cell surface is an annular ring, 2 mm to the outside of the polar axis (Shaw et al, 2000). In the pollen tube we suggest that when the fringe is destroyed with Lat-B, vesicles are no longer precisely targeted but randomly dock across the apical domain.…”
Section: Discussionmentioning
confidence: 86%
“…A targeted secretion could have the effect of locally weakening the cell wall and allowing turgor-driven cell expansion. In this regard it is pertinent that studies of root hairs, which like the pollen tubes grow by tip expansion, show that the region of maximal shape change at the cell surface is an annular ring, 2 mm to the outside of the polar axis (Shaw et al, 2000). In the pollen tube we suggest that when the fringe is destroyed with Lat-B, vesicles are no longer precisely targeted but randomly dock across the apical domain.…”
Section: Discussionmentioning
confidence: 86%
“…Approximately the first third of root hair growth may be non-pulsatile and slower than the later pulsatile phase (Wymer et al, 1997), yet in another species, growth was reportedly non-pulsatile throughout hair elongation (Shaw et al, 2000). Thus, again pulsatile growth is apparently neither obligatory nor common in this tip-growing cell type.…”
Section: Absence Of Pulsatile Growthmentioning
confidence: 92%
“…However, the PME data in tobacco challenge this view by showing that the inverted cone stains much less brightly than the flanks surrounding the cone ; data herein). It is possible that material moves forward along the edge of the cell, being directed by the cortical actin fringe (Lovy-Wheeler et al, 2005), and deposits as an annulus outside of the polar axis (Bove et al, 2008;Zonia and Munnik, 2008), as has been shown for root hairs (Shaw et al, 2000;Dumais et al, 2004). This is an attractive idea, but more work is needed to establish its occurrence in pollen tubes.…”
Section: Exocytosis Has Been Studied In Other Pollen Tubesmentioning
confidence: 98%